Nomograms for Death from Pneumocystis jirovecii Pneumonia in HIV-Uninfected and HIV-Infected Patients - Feng Q; Hao J; Li A; Tong Z (International Journal of General Medicine, 2022)
Qiuyue Feng,1,2 Jingjing Hao,3 Ang Li,3 Zhaohui Tong1 1Department of Respiratory and Critical Care Medicine, Beijing Institute of Respiratory Medicine, Beijing Chaoyang Hospital, Capital Medical University, Beijing, 100020, People’s Republic of China; 2Department of Respiratory Medicine, Beijing Huairou Hospital, Beijing, 101400, People’s Republic of China; 3Department of Critical Care Medicine, Beijing Ditan Hospital, Capital Medical University, Beijing, 100015, People’s Republic of ChinaCorrespondence: Zhaohui Tong, Department of Respiratory and Critical Care Medicine, Beijing Institute of Respiratory Medicine, Beijing Chaoyang Hospital, Capital Medical University, Beijing, 100020, People’s Republic of China, Email tongzhaohuicy@sina.com Ang Li, Department of Critical Care Medicine, Beijing Ditan Hospital, Capital Medical University, Beijing, 100015, People’s Republic of China, Email liang@ccmu.edu.cnPurpose: Pneumocystis jirovecii pneumonia (PCP) is a major cause of death in immunocompromised patients. Many risk factors for poor prognosis have been reported, but few studies have created predictive models with these variables to calculate the death rate accurately. This study created nomogram models for the precise prediction of mortality risk in human immunodeficiency virus (HIV) uninfected and HIV-infected patients with PCP.Patients and Methods: A retrospective study was performed over a 10-year period to evaluate the clinical characteristics and outcomes of PCP in HIV-uninfected and HIV-infected adults treated in Beijing, China from 2010 to 2019. Univariate and multivariate logistic regression analyses were used to identify mortality risk factors to create the nomograms. Nomogram models were evaluated by using a bootstrapped concordance index, calibration plots and receiver operating characteristic (ROC) curves.Results: A total of 167 HIV-uninfected and 193 HIV-infected PCP patients were included in the study. Pneumothorax, duration of fever after admission, CD4+ T cells ≤ 100/μL and trimethoprim-sulfamethoxazole (TMP-SMX) combined with caspofungin (CAS) treatment were independent risk factors for death in HIV-uninfected PCP patients. We derived a well calibrated nomogram for mortality by using these variables. The area under the curve was 0.865 (95% confidence interval 0.799– 0.931). Independent risk factors for death in HIV-infected PCP patients were pneumothorax, platelet (PLT) ≤ 80× 109/L, haemoglobin (HGB) ≤ 90 g/L, albumin (ALB), cytomegalovirus (CMV) coinfection and TMP-SMX combined with CAS treatment. The nomogram showed good discrimination, with a C-index of 0.904 and excellent calibration.Conclusion: The nomograms which were derived may be useful tools for the precise prediction of mortality in HIV-uninfected and HIV-infected patients, but require validation in clinical practice.Keywords: Pneumocystis jirovecii pneumonia, nomogram, HIV, HIV-uninfected, mortality